Dinamika Self-Compassion pada Wanita Penderita Psoriasis Usia Emerging Adulthood (Jurnal Ilmiah Psikologi MIND SET, 2024)
Psoriasis is an autoimmune disease that causes chronic inflammation of the skin and joints that affects individuals genetically and cannot be completely cured. This research needs to be done because self-compassion is stated to have an important role in self-adjustment to chronic skin conditions so that it can be a therapy to reduce psychological distress in sufferers. Self-compassion refers to how individuals relate to themselves in the face of failure, disability, life challenges, or suffering, feel connected to others who also suffer, and understand and support themselves during difficult times. The purpose of this generic qualitative research is to get an overview of the dynamics of self-compassion in women who suffer from psoriasis and are in early adulthood. In-depth interviews were conducted with three women with psoriasis aged 18-29 years about their experiences with psoriasis. Conclusion: all subjects of this study, namely emerging adulthood women who experience psoriasis, have shown self-compassion with a description of positive and negative behaviors that match the main dimensions of Neff's Self-Compassion Theory, namely self-kindness; self-judgement; common humanity; isolation; mindfulness; overidentification/avoidance. They always try to make progress in a more positive direction. Research findings: social support, self-acceptance, negative emotions, anxiety disorders. Research implications and limitations, theoretical and practical suggestions are also discussed.